THE EFFECT OF FIRM SIZE, LEVERAGE, PROFITABILITY, LIQUIDITY AND DIVIDEND POLICY ON FIRM VALUE ON NON-CYCLICAL CONSUMER SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2019-2022 - Audrey Deliana; Linda Santioso (International Journal of Application on Economics and Business, 2024)
This research was aimed with obtaining empirical evidence regarding the significant influence of the independent variables, namely company size (total assets), Leverage (DER), Profitability (ROE), Liquidity (CR) and Dividend Policy (DPR) and the dependent variable used namely Company Value (PBV). The population used in this research are companies with non-cyclical consumer sectors listed on the Indonesia Stock Exchange (BEI) in 2019 - 2022. This research uses quantitative descriptive research methods to test hypotheses. The sample selection technique used in this research was purposive sampling, where the sample obtained was 19 companies. The data used is secondary data processed using the SPSS version 27 program. The results of this research show that Leverage, Profitability, and dividend policy have a significant positive effect on company value, while company size and liquidity have no effect on company value.